Expression of Kidney White Rats Diabetes Mellitus after Therapy of Sinom Ethyl Acetate Fraction Mixed Lime and Honey - Wiradnyani, Ni Ketut (MultiTech Publisher, 2024)
This study aims to prove that the administration of the ethyl acetate fraction sinom mixture of lime and honey (SCJM) can improve the histological structure of the kidney of Spraque Dawley rats (SD) diabetic were divided into six groups with four replications each. The K1 group as a positive control was not given a sample, the K2 group was given a sample dose of 50 mg/kg BW, the K3 group was given a sample dose of 100 mg/kg BW, and the K4 group was given a sample dose of 150 mg/kg BW, the K5 group was given an extract dose of 200 mg/kg BW, and positive control group K6 which was carried out for 21 days. The rats were then sacrificed and the kidney organs were taken for histopathological preparation with Hematoxylin Eosin (HE) staining. The results showed that there was fatty degeneration and necrosis of the kidneys. Kruskal Wallis test results from all treatments showed p = 0.001 for both fatty degeneration and necrosis (p<0.05).abstract is written along 100-200 words with a single space. Abstract content must explain the subject matter discussed in the article, the method used, the results or findings and conclusions